STUDENTS ATTITUDE TO CONSERVE MEDICINAL PLANTS AND ENVIRONMENT IN CIPANAS: PROFILE AND COMPARATIVE ANALYSIS - Ichsan, Ilmi Zajuli; Sigit, Diana Vivanti; Ristanto, Rizhal Hendi; Luthfi, Ilena Amalia; Muharomah, Dewi Robiatun; Efendi, Muhammad (International Journal of Indonesian Education and Teaching (IJIET), 2019)
Students' awareness in conserving medicinal plants and the environment is still the focus of discussion among educators. Especially in students at vocational school levels who do not receive comprehensive Biology learning. The purpose of this study was to measure students' attitudes in conserving medicinal plants and the environment. The research method used is descriptive method with survey techniques. The study was conducted in March-April 2019 at Cipanas State 1 Vocational High School, Cianjur, West Java, Indonesia. The sample used was selected by simple random sampling, obtained as many as 104 students divided into 44 male and 60 female students. The results showed that the average score of students' attitudes was 76.47. The indicator with the highest score is related to the program of planting medicinal plants in the home yard. While the lowest indicators relate to conservation policies for medicinal plants and the environment. This is because the information received by students in terms of conservation policy is still need to be improve. The conclusion of this study is that the scores of student attitudes regarding the conservation of medicinal plants and the environment are good, but in some indicators still need to be improved.DOI: doi.org/10.24071/ijiet.2019.030202